2020
DOI: 10.3390/ijerph17041208
|View full text |Cite
|
Sign up to set email alerts
|

Micronucleus Frequency in Exfoliated Buccal Cells of Children Living in an Industrialized Area of Apulia (Italy)

Abstract: Micronuclei (MN) are biomarkers of early biological effect often used for detecting DNA damage in human population exposed to genotoxic agents. The aim of this study was to evaluate the frequency of MN in exfoliated buccal cells of children living in an industrialized (impacted) area compared with that found in children living in a control area without significant anthropogenic impacts. A total of 462 6–8-year-old children (206 in the impacted area, 256 in the control area) attending primary school were enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 59 publications
1
12
0
1
Order By: Relevance
“…Conversely, this study design did not allow to compare the MN and comet test results at high and low air pollutants levels. Various studies found a positive association between air pollution and DNA damage tests at lower levels of air pollutants than that found in our study [40][41][42][43][44][45][46][47][48][49]. However, other studies provided negative or inconsistent results regarding the association between MN frequency in children's cells and air pollutant exposure, highlighting the role of other behavioural factors in the MN occurrence [47,52,53].…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Conversely, this study design did not allow to compare the MN and comet test results at high and low air pollutants levels. Various studies found a positive association between air pollution and DNA damage tests at lower levels of air pollutants than that found in our study [40][41][42][43][44][45][46][47][48][49]. However, other studies provided negative or inconsistent results regarding the association between MN frequency in children's cells and air pollutant exposure, highlighting the role of other behavioural factors in the MN occurrence [47,52,53].…”
Section: Discussionsupporting
confidence: 47%
“…A previous study conducted on preschool children (3-6 years old) living in the same town [39] during two consecutive winters, also found a high mean MN frequency in children's buccal mucosa cells, similarly to that found in present study. Other studies evaluated the frequency of MN in exfoliated buccal cells in children [40][41][42][43][44][45][46][47][48][49] and found a significant association between MN frequencies and various air pollutants in children exposed to air pollution.…”
Section: Discussionmentioning
confidence: 99%
“…There is ample evidence that regular and sufficient physical activity, as well as low levels of sedentary behaviour, are important for growth and health in school-aged children and youth [1][2][3], and contribute to the avoidance or limitation of risk of many conditions for chronic or degenerative diseases, which can occur even into adulthood [4,5]. Insufficient physical activity and too much sedentary time, on the other hand, have been associated with poor physical and mental health [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In this way, it would be possible to identify people who actually suffered damages caused by airborne chemicals and this data could be correlated with the risk of ASD. For example, micronuclei could be considered, as they are biomarkers of early biological effect which can detect the presence of initial (and reversible) alterations in the chromosomal structure and oxidative damage to DNA caused by air pollution exposure [55,56].…”
Section: Discussionmentioning
confidence: 99%